2008
DOI: 10.1097/aln.0b013e31817b5a9b
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Impact of Intravenous Lidocaine on Analgesia, Functional Recovery, and Nociceptive Pain Threshold after Total Hip Arthroplasty

Abstract: Low dose perioperative intravenous lidocaine after total hip arthroplasty offers no beneficial effect on postoperative analgesia and does not modify pressure and tactile pain thresholds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
3
13

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(105 citation statements)
references
References 35 publications
3
86
3
13
Order By: Relevance
“…24 Seven studies originated in the USA, [25][26][27][28][29][30][31] one in Belgium, 32 two in Taiwan, 14,33 three in Germany, 23,34,35 one in New Zealand, 36 three in Sweden, [37][38][39] two in China, 40,41 one in France, 42 three in Canada, [43][44][45] one in Mexico, 24 two in Saudi Arabia, 46,47 one in Israel, 48 one in the Republic of Korea 49 and one in Finland. 50 Studies were conducted in patients undergoing abdominal, cardiac, thoracic, orthopedic, or urologic surgery ( Table 1).…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…24 Seven studies originated in the USA, [25][26][27][28][29][30][31] one in Belgium, 32 two in Taiwan, 14,33 three in Germany, 23,34,35 one in New Zealand, 36 three in Sweden, [37][38][39] two in China, 40,41 one in France, 42 three in Canada, [43][44][45] one in Mexico, 24 two in Saudi Arabia, 46,47 one in Israel, 48 one in the Republic of Korea 49 and one in Finland. 50 Studies were conducted in patients undergoing abdominal, cardiac, thoracic, orthopedic, or urologic surgery ( Table 1).…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…50 Studies were conducted in patients undergoing abdominal, cardiac, thoracic, orthopedic, or urologic surgery ( Table 1). Source of sponsorship was not mentioned in 11 studies, [23][24][25][26][27]29,42,[45][46][47][48] while other studies received grants from foundations, national councils, or universities. No study reported industry sponsorship.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations